Insight: The interpretation of Islam within the legal framework of the Indigenous Malaya - Wan Ahmad Fauzi, Wan Husain (Penerbit Universiti Malaysia Pahang, 2021)
This article promotes Islam's interpretation within the legal framework of the indigenous Malayan based on its principle of sovereignty. At present, Islam is popularly defined by the Court's decision in Che Omar Che Soh vs Public Prosecutor, where the sovereignty of the Malay Rulers was made as a parameter in interpreting Islam within the context of Article 3 of the Federal Constitution. The said decision confines Islam only in the context of personal laws due to the Pangkor Treaty, 1874. This is a qualitative study applying the legal history design. The findings showed that the indigenous sovereignty sourced from the Islamic teachings had not been affected despite the introduction of the doctrine of advice and various British policies throughout their intervention in Malaya. In fact, many agreements made between the Malay Rulers and the British retained the indigenous sovereignty as those agreements were subjected to the old Malayan Constitution, the principle of Islam as the law of the land as well as contemporary local thinking. The above three local circumstances explained the principle of sovereignty, thus the position of Islam in the indigenous Malaya's legal framework. This article concludes that the accurate interpretation of Islam should be based on the al-Qur'an and al-Sunnah because the Malay Rulers have retained their position as caliph even after the British intervened in their internal state affairs.